2016
DOI: 10.1590/1807-3107bor-2016.vol30.0091
|View full text |Cite
|
Sign up to set email alerts
|

Civil liability: characterization of the demand for lawsuits against dentists

Abstract: In light of the fact that dentists may be held civilly liable for their practice, it is important to understand the current situation of lawsuits filed against these professionals by studying current legal decisions and the literature. The objective of this study was to analyze the case law of the Court of Justice of São Paulo, Brazil, relative to the profile of patients and professionals, the most commonly involved specialties, the amounts litigated and the court decisions pertaining to civil liability lawsui… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

12
21
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(36 citation statements)
references
References 8 publications
12
21
0
3
Order By: Relevance
“…The result of 42.2% of legal entities as defendants agrees with the study by Zanin et al (20), which indicated 49.48% of legal entities in a survey conducted between May 2013 and April 2014. The predominance of legal entities as defendants was also verified in the study by Ferreira et al (24), 77.4%.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…The result of 42.2% of legal entities as defendants agrees with the study by Zanin et al (20), which indicated 49.48% of legal entities in a survey conducted between May 2013 and April 2014. The predominance of legal entities as defendants was also verified in the study by Ferreira et al (24), 77.4%.…”
Section: Discussionsupporting
confidence: 91%
“…The percentage of faulty sentences was compatible with that found by Zanin et al. , 44.32% in 43 cases, L. Bjorndal & C. Reit , 43%, Castro et al. , 47%, Bouchardet et al.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…There are still no reports of late mandibular fracture after third molar extraction in the literature with Stafne bone cyst, with the most frequent lesions being dentigerous and radicular cyst 9,10. In other studies, half of the fractures occurred had associated cystic lesions, and most of the cases analyzed by Grau-Manclús (2011) were related to cysts or pericoronal capillary thickening of impacted third molars [11]. However, the longer the time of impacting the tooth, the greater the risk of developing cysts.…”
mentioning
confidence: 88%